Single cell genomics indicates horizontal gene transfer and viral infections in a deep subsurface Firmicutes population - Labonté, Jessica M.; Field, Erin K.; Lau, Maggie; Chivian, Dylan; Van Heerden, Esta; Wommack, K. Eric; Kieft, Thomas L.; Onstott, Tullis C.; Stepanauskas, Ramunas (Frontiers in Microbiology, 2015)
A major fraction of Earth's prokaryotic biomass dwells in the deep subsurface, where cellular abundances per volume of sample are lower, metabolism is slower, and generation times are longer than those in surface terrestrial and marine environments. How these conditions impact biotic interactions and evolutionary processes is largely unknown. Here we employed single cell genomics to analyze cell-to-cell genome content variability and signatures of horizontal gene transfer (HGT) and viral infections in five cells of Candidatus Desulforudis audaxviator, which were collected from a three km-deep fracture water in the 2.9 Ga-old Witwatersrand Basin of South Africa. Between 0 and 32 % of genes recovered from single cells were not present in the original, metagenomic assembly of Desulforudis, which was obtained from a neighboring subsurface fracture. We found a transposable prophage, a retron, multiple clustered regularly interspaced short palindromic repeats (CRISPRs) and restriction-modification systems, and an unusually high frequency of transposases in the analyzed single cell genomes. This indicates that recombination, HGT and viral infections are prevalent evolutionary events in the studied population of microorganisms inhabiting a highly stable deep subsurface environment.